Association of variants in MMEL1 and CTLA4 with rheumatoid arthritis in the Han Chinese population. Issue 10 (21st July 2011) - Danoy, Patrick; Wei, Meng; Johanna, Hadler; Jiang, Lei; He, Dongyi; Sun, Linyun; Zeng, Xiaofeng; Visscher, Peter M; Brown, Matthew A; Xu, Huji
Abstract : Background: The genome-wide association study era has made great progress in identifying susceptibility genes and genetic loci for rheumatoid arthritis (RA) in populations of White European ancestry. However, few studies have tried to dissect disease aetiopathogenesis in other ethnic populations. Objective: To investigate these associations in the Han Chinese population. Methods: Haplotypes from the HapMap database Chinese population were used to select tag-single-nucleotide polymorphisms (SNPs) (r 2 =0.8) across 19 distinct RA genomic regions. A two phase case–control association study was performed, with 169 SNPs genotyped in phase I (n=571 cases, n=880 controls), and 64 SNPs achieving p<0.2 in the first phase being genotyped in phase II (n=464 cases, n=822 controls). Association statistics were calculated using permutation tests both unadjusted and adjusted for the number of markers studied. Results: Robust association was detected for MMEL1 and CTLA4, and modest association was identified for another six loci: PADI4, STAT4, PRDM1, CDK6, TRAF1-C5 and KIF5A-PIP4K2C . All three markers genotyped in MMEL1 demonstrated association, with peak signal for rs3890745 (p=2.6×10 −5 unadjusted, p=0.003 adjusted, OR=0.79). For CTLA4, significance was detected for three of five variants showing association, with peak association for marker rs12992492 (p=4.3×10 −5 unadjusted, p=0.0021 adjusted, OR=0.77). Lack of association of common variants in PTPN22 with RA in Han Chinese was confirmed. Conclusion: This study identifies MMEL1 and CTLA4 as RA susceptibility genes, provides suggestive evidence of association for a further six loci in the Han Chinese population and confirms lack of PTPN22 association in Asian populations. It also confirms the value of multiethnic population studies to help dissect disease aetiopathogenesis.